Estimation of Carbon Content in Mangrove Litter in the Forest of Dabong Village, Kubu Raya Regency - Putri Annisa Rachmawati; Ikha Safitri; Arie Antasari Kushadiwijayanto (Buletin Oseanografi Marina, 2026)
Mangrove ecosystems have a huge potential in controlling the effects of global warming through their ability to absorb carbon dioxide (CO2) from the atmosphere. Mangrove litter is one component that becomes a carbon sink, contributing to the transfer and storage of organic carbon in coastal sediments. This study aims to calculate the rate of mangrove litter production and the rate of carbon production in mangrove litter in the Forests of Dabong Village, Kubu Raya Regency. Mangrove litter was collected using a 1x1 m2 litter trap with a mesh size of 0.2 cm over a period of 15 days. The results of the study show that the rate of mangrove litter production is 15.01 tons/ha/year - 28.88 tons/ha/year, with leaf litter being the dominant fraction compared to twigs, flowers, and fruits.. The carbon content percentage of the litter samples obtain was 45.24%, with an estimated carbon production rate in the Forest of Dabong Village ranging from 7.69 tons C/ha/year to 12.92 tons C/ha/year. Leaf litter contributed the highest proportion of carbon production due to its greater biomass contribution and continous turnover. These findings highest the significant role of Dabong Village mangroves in coastal carbon sequestration and climate change mitigation.. Furthermore, the results are consistent with regional patterns of mangrove carbon dynamics, reinforcing the importance of conserving and sustainability managing mangrove forests as part of blue carbon strategies to reduce atmospheric CO2 concentrations and enhance long-term carbon storage in coastal environments.